Impaired anti-inflammatory function of apolipoprotein A-II concentrations predicts metabolic syndrome and diabetes at 4 years follow-up in elderly Turks - Onat, Altan; Hergenc, Guelay; Ayhan, Erkan; Ugur, Murat; Can, Guenay (WALTER DE GRUYTER & CO, 2009)
Background: We evaluated prospectively the predictive value of serum apolipoprotein (apo) A-II, the second major apolipoprotein of high-density lipoprotein (HDL), for cardiometabolic risk in Turkish adults showing abnormalities in other proteins that normally confer protection. Methods: Determinants of apoA-II and its associations with coronary heart disease (CHD), metabolic syndrome (MetS) and diabetes were investigated at 4 years follow-up in 193 elderly men and women. Results: ApoA-II concentrations at baseline, in addition to being significantly related to HDL-cholesterol, were directly associated with complement C3 in multivariate linear regression analyses comprising nine variables. Following adjustment for gender, age and HDL-cholesterol (>30/>33 g/L, in men and women, respectively), low serum apoA-II concentrations predicted incident MetS [relative risk (RR) 3.5 (95% CI 1.4; 8.6)] and type 2 diabetes [RR 4.5 (95% CI 1.3; 15.6)] in both genders at an increment of 1 SD. Increased apoA-II values were not associated with prevalent or incident CHD, and tended to be marginally atheroprotective only in males. Conclusions: Serum apoA-II concentrations confer risk for MetS and diabetes and exhibit evidence of anti-inflammatory properties among Turks. These findings support the effects seen for several other HDL protein constituents. This finding may explain the increased cardiometabolic risk among Turks. Clin Chem Lab Med 2009; 47: 1389-94.
Keywords: apolipoprotein A-II; coronary heart disease; diabetes; metabolic syndrome; proinflammatory state; CORONARY-ARTERY-DISEASE; INSULIN-RESISTANCE; SERUM ADIPONECTIN; TRANSGENIC MICE; RISK; CHOLESTEROL; LIPOPROTEIN; PLASMA; HDL; ASSOCIATION; Medical Laboratory Technology